2021
DOI: 10.3390/jmse9070783
|View full text |Cite
|
Sign up to set email alerts
|

Maritime Broadband Communication: Wireless Channel Measurement and Characteristic Analysis for Offshore Waters

Abstract: For a long time, the development of maritime communication has been restricted by the low data rate, high-latency and high cost of the current communication systems. The upgrade of new generation mobile communication technologies is attracting more and more attention to conduct a shore-based broadband mobile communication network with high-latency and high reliability to serve the maritime industries. This paper presents a solution by means of building a ship-to-infrastructure (S2I) and a ship-to-ship (S2S) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Li et al [12] conducted wireless channel measurement and analysis on the shipping environment and found that bridges, buildings, and large ships would have a signifcant infuence on wireless channels. Tey conducted channel measurements on wireless channels between shipto-ship and ship-to-infrastructure [13,14]. Te results showed that the main factor afecting the root mean square delay spread in the maritime wireless channel without other obstacles is the communication between transmitting and receiving.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [12] conducted wireless channel measurement and analysis on the shipping environment and found that bridges, buildings, and large ships would have a signifcant infuence on wireless channels. Tey conducted channel measurements on wireless channels between shipto-ship and ship-to-infrastructure [13,14]. Te results showed that the main factor afecting the root mean square delay spread in the maritime wireless channel without other obstacles is the communication between transmitting and receiving.…”
Section: Introductionmentioning
confidence: 99%